2019
DOI: 10.1111/epi.16370
|View full text |Cite
|
Sign up to set email alerts
|

GATORopathies: The role of amino acid regulatory gene mutations in epilepsy and cortical malformations

Abstract: The mechanistic target of rapamycin (mTOR) pathway has been implicated in a growing number of malformations of cortical development (MCD) associated with intractable epilepsy. Mutations in single genes encoding mTOR pathway regulatory proteins have been linked to MCD such as focal cortical dysplasia (FCD) types IIa and IIb, hemimegalencephaly (HME), and megalencephaly. Recent studies have demonstrated that the GATOR1 protein complex, comprised of DEPDC5, NPRL3, and NPRL2, plays a pivotal role in regulating mTO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 67 publications
2
34
1
1
Order By: Relevance
“…Given that the brain MRI and PET were normal, the MCD may be related only to altered cortical lamination in this patient, although the tissue was not biopsied so could not be confirmed by histopathology. The clinical manifestations in this case were consistent with those of NPRL3 variants reported in the literature [1] , [2] . Intellectual function, neurological examination, and neuroimaging were normal.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Given that the brain MRI and PET were normal, the MCD may be related only to altered cortical lamination in this patient, although the tissue was not biopsied so could not be confirmed by histopathology. The clinical manifestations in this case were consistent with those of NPRL3 variants reported in the literature [1] , [2] . Intellectual function, neurological examination, and neuroimaging were normal.…”
Section: Discussionsupporting
confidence: 90%
“…NPRL3 (nitrogen permease regulator-like 3) variants have been linked to familial focal cortical dysplasia type II, which is pathologically characterized by dysmorphic neurons and balloon cells [1] , [2] . Mutations in the NPRL3 gene cause an autosomal dominant familial focal epilepsy with variable foci (FFEVF) characterized by focal seizures originating from different cortical regions, including temporal, frontal, parietal, and occipital lobes [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent sequencing studies revealed that somatic brain mutations in mTOR regulators including mTOR itself, PIK3CA , RHEB , AKT3 , TSC1 , and TSC2 [79-82] can result in FCD (Table 1) [81, 83]. In addition, mutations in DEPDC5 , NPRL2 , and NPRL3 , which are components of the mTORC1 inhibitor GATOR complex 1 [84], have been linked to FCD, infantile spasms, focal epilepsy, and sudden unexpected death in epilepsy [85-87].…”
Section: Mtoropathiesmentioning
confidence: 99%
“…[31][32][33][34] More specifically, it has been described in various lesional and nonlesional epileptic disorders such as familial focal epilepsy with variable foci or ADNFLE. [31][32][33][34][35][36] The "two-hit" mutational hypothesis may explain the presence of the c.77C>T (p. Thr26Met) variant in CHRNB2 in the asymptomatic father of one of our patients. While both this patient and her father are carrying the c.77C>T (p. Thr26Met) germline variant in CHRNB2, only she would by carrying the second, somatic, CHRNB2 variant in her brain cells resulting in the epileptogenesis.…”
Section: Discussionmentioning
confidence: 99%